Environmental and Technological Threats in the Arctic Region - Csenkey, Kristen | https://orcid.org/0000-0002-4074-2602 (Taylor & Francis, 2026)
Arctic subregions have undergone major structural changes in the past few decades. Looking past traditional military and geopolitical understandings of these regions, this book focuses rather on climate change and on the emergence of the digital economy and its infrastructures as two of the most fundamental challenges for Arctic communities and inhabitants. To this end, Section I, on Arctic (re)newned environment, focuses on the acceleration of permafrost thaw, protection of submarine cables, and the importance of an all-domain military approach. Section II analyses infrastructure challenges linked to this “new” Arctic environment, providing examples within maritime, transportation, and digital-physical infrastructures. Finally, Section III provides results of research focusing on the emerging geopolitical and strategic threats posed by data routes, technological dependencies, cryptocurrency mining, and disinformation. Over the course of the book, authors offer practical insights into how to tackle these threats, lessons learned, best practices, and recommendations. By bringing together analyses from a range of authors from different interdisciplinary backgrounds, the book provides a holistic understanding of these phenomena. This volume will be useful for students, scholars, and researchers of Arctic studies, environmental governance, and environmental security.